Oral history w Rosji i Polsce – próba porównania: Oral history in Russia and Poland – comparison attempt - Lewandowska, Izabela; Giżejewski, Gracjan (Przegląd Wschodnioeuropejski, 2019)
The aim of this article is to note the similarities and differences in the oral history of Russia and Poland. It is based on academic literature and the public presence of oral history in both countries, and analyzes the development of research on oral history as well as shows the presence of this method in academic studies. It also presents the non-governmental activities of social organizations. The comparative studies arrive at the conclusion that oral history centers in Russia are developing vigorously on the institutional (academic) level, whereas in Poland more on the council and civic levels. It is important to establish a collaboration between researchers from both countries in order to improve the method and run common projects on that matter.